(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Bladder cancer (BC) remains one of the predominant pathologies in onco-urological practice and poses a significant challenge for global healthcare. Understanding the risk factors and prognosis of this disease can improve prevention, early detection, and treatment of this type of cancer.